Eremobiotus ginevrae sp. nov. and Paramacrobiotus pius sp. nov., two new species of Eutardigrada - Lisi, Oscar; Binda, Maria Grazia; Pilato, Giovanni (Zootaxa, 2016)
Two new eutardigrade species are described: Eremobiotus ginevrae sp. nov. and Paramacrobiotus pius sp. nov. The first is similar to Eremobiotus alicatai (Binda, 1969) but differs in the claw shape and dimensions. It has been found in Sicily, Israel and Russia. The second species, belonging to the richtersi group, is currently found exclusively in Sicily. It has a smooth cuticle, three macroplacoids and a microplacoid, eggs with reticulated trunco-conical processes with small terminal thorns; the egg-shell is areolated and the areolae are clearly sculptured.